Photoredox-catalyzed stereoselective alkylation of enamides with N-hydroxyphthalimide esters via decarboxylative cross-coupling reactions - Guo, Jing-Yu (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Stereoselective β-C(sp(2))–H alkylation of enamides with redox-active N-hydroxyphthalimide esters via a photoredox-catalyzed decarboxylative cross-coupling reaction is demonstrated. This methodology features operational simplicity, broad substrate scopes, and excellent stereoselectivities and functional group tolerance, affording a diverse array of geometrically defined and synthetically valuable enamides bearing primary, secondary or tertiary alkyl groups in satisfactory yields.